Youth Pathways into Cybercrime - Aiken, Mary (Europol, 2016)
This research project was established to draw together existing, recent evidence on online behaviour and associations with criminal and antisocial behaviour amongst young people. Specifically, it was designed to explore the trajectories and pathways that lead to ‘cyber-criminality’ through a series of mixed-methodological endeavours and the integration of theoretical frameworks across criminology and psychology, including cyberpsychology and computer science.